Finding Data Pathways Through the ‘Pandemic Pilgrimage Boom’: Embedded-like Research, COVID-19, and the British Pilgrimage Trust - Eleanor O’Keeffe (International Journal of Religious Tourism and Pilgrimage, 2024)
This article reviews claims that the United Kingdom experienced a ‘pandemic pilgrimage boom’. It contributes findings from an ‘embedded-like’ research project, which drew on data created by the British Pilgrimage Trust (BPT) – a heritage and wellbeing charity that hosts a website hub to support pilgrimage action in the UK – to debate about the impact of COVID-19 on pilgrimage practice. These findings show how a set of uses and meanings about pilgrimage, particularly its affordances for mental health and emotional wellbeing, have resonated during the pandemic, especially at moments of heightened social stress. This has generated greater social traction for pilgrimage, and there may be potential for further growth in response to twenty-first century crises, such as the increasingly apparent impacts of climate change. Learning from the experience of COVID-19, this article encourages research investment in longitudinal data-driven approaches to study the individual and social affordances that pilgrimage offers in view of its modern adaptations and applications.